UMPSA explores collaboration with Tsukuba University - Mimi Rabita, Abd Wahit (UMPSA, 2024)
TOKYO, 15 December 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is exploring a collaboration with Tsukuba University, Japan, to implement the Mission for an Inclusive Ecosystem of Sustainable Community International Networking (MEiJALIN) programme.